PENINGKATAN PROSES DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL EXAMPLE NON EXAMPLE PADA PEMBELAJARAN MATEMATIKA KELAS V DI SDN 025/II MUARA BUNGO - Andina Pitri, Wahyuni; Nurlev Avana; Dhini Mufti (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
The research is based on the monotonous process of learning mathematics, in addition to finding that teachers do not use image media in teaching, and there are still students who consider mathematics learning difficult. The purpose of the research is to improve the process and outcomes of learning by using Example Non Example in Mathematics education for 5th grade at SDN 025/II Muara Bungo. This research is classroom action research (CAR) conducted in 2 cycles, each cycle consisting of 2 meetings. The subjects of the research are 15 students from 5th grade at SDN 025/II Muara Bungo, consisting of 9 boys and 6 girls. The results of the study show an improvement in the process and outcomes of students through Example Non Example. The results of the teacher observation sheet in cycle I were 80% and in cycle II increased to 95%. The results of the student observation sheet in cycle I were 70% and in cycle II increased to 96.5%. The results of the test scores in cycle I were 60% and in cycle II were 80%. It can be concluded that Example Non Example can improve the process and learning outcomes in Mathematics education.